Предмет: Алгебра, автор: Аноним

Помогите пожалуйста !!!!!!!​

Приложения:

Ответы

Автор ответа: Miroslava227
0

Ответ:

1.

z = 2 {x}^{3}  {y}^{4}  - 3 {x}^{4}   + 2y - 6 \\

z'_x = 6 {x}^{2} {y}^{4}  - 12 {x}^{3}   \\ z'_y = 8 {y}^{3}  {x}^{3}  + 2

2.

f(x,y) =  \frac{4x - 3y}{2x + y}  \\

f'_x =  \frac{(4x - 3y)'_x(2x + y) - (2x + y)'_x(4x - 3y)}{ {(2x + y)}^{2} }  =  \\  =  \frac{4(2x + y) - 2(4x - 3y)}{ {(2x + y)}^{2} }  =  \frac{8x - 4y - 8x + 6y}{ {(2x + y)}^{2} }  =  \\  =  \frac{2y}{ {(2x + y)}^{2} }

f'_y =  \frac{(4x - 3y)'_y(2x + y) - (2x + y)'_y(4x - 3y)}{ {(2x + y)}^{2} }  =  \\  =  \frac{ - 3(2x + y) - 1 \times (4x - 3y)}{ {(2x + y)}^{2} }  =  \\  =  \frac{ - 6x - 3y - 4x + 3y}{ {(2x + y)}^{2} }  =  \frac{ - 10x}{ {(2x + y)}^{2} }

4.

\psi(x,y) =  {e}^{x} (2x - 3y)

\psi'_x = ( {e}^{x} )'(2x - 3y) + (2x - 3y)'_x \times  {e}^{x}  =  \\  =  {e}^{x} (2x - 3y) + e {}^{x}  \times 2 =  {e}^{x} (2x - 3y + 2)

\psi'_y =  {e}^{x}(2x - 3y)'_y =  - 3 e {}^{x}

5.

\phi(x,y) =  ln(6 {x}^{2}y {}^{5}  )

\phi'_x =  \frac{1}{6 {x}^{2}  {y}^{5} }  \times 12x {y}^{5}  =  \frac{2}{x}  \\

\phi'_y =  \frac{1}{6 {x}^{2} {y}^{5}  }  \times 5 {y}^{4}  \times 6 {x}^{2}  =  \frac{5}{y}  \\

Похожие вопросы